1996
DOI: 10.1046/j.1471-4159.1996.67041401.x
|View full text |Cite
|
Sign up to set email alerts
|

Up‐Regulation of Functional Voltage‐Dependent Sodium Channels by Insulin in Cultured Bovine Adrenal Chromaffin Cells

Abstract: Treatment of cultured bovine adrenal chromaffin cells with 100 nM insulin raised [3H]saxitoxin ([3H]STX) binding in a time‐dependent manner (t1/2 = 26 h). Insulin (100 nM for 4 days) increased the Bmax of [3H]STX binding by 49% without changing the KD value and also augmented the maximal influx of 22Na+ due to 560 µM veratridine by 39% without altering the EC50 value of veratridine. The stimulatory effect of insulin on 22Na+ influx was concentration‐dependent with an EC50 of 3 nM, whereas insulin‐like growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
44
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 45 publications
10
44
0
Order By: Relevance
“…In auditory and visual circuits in brain, axonal conduction velocity was decreased in streptozotocin-induced diabetic rats; insulin treatment with its subcutaneous implants, initiated 6 months after streptozotocin-induced diabetes mellitus, almost completely reversed the existing abnormalities in brain, whereas normalization of blood glucose levels had no effect (10). Because Na + channel is essential to generation and conduction of action potential, up-regulation of cell surface Na + channel by insulin demonstrated in our study (28) may be instructive in understanding the regenerative effect of insulin in diabetic neuropathy. More surprisingly, the axon guidance role of insulin receptor was evidenced by Song et al (84) in the photoreceptor of the fruit fly Drosophila; insulin receptor signaling was required for the extending neuronal axon to find its way from the retina to the brain during development of visual system.…”
Section: Physiological Roles Of Insulin Receptor and Igf-i Receptor Isupporting
confidence: 48%
“…In auditory and visual circuits in brain, axonal conduction velocity was decreased in streptozotocin-induced diabetic rats; insulin treatment with its subcutaneous implants, initiated 6 months after streptozotocin-induced diabetes mellitus, almost completely reversed the existing abnormalities in brain, whereas normalization of blood glucose levels had no effect (10). Because Na + channel is essential to generation and conduction of action potential, up-regulation of cell surface Na + channel by insulin demonstrated in our study (28) may be instructive in understanding the regenerative effect of insulin in diabetic neuropathy. More surprisingly, the axon guidance role of insulin receptor was evidenced by Song et al (84) in the photoreceptor of the fruit fly Drosophila; insulin receptor signaling was required for the extending neuronal axon to find its way from the retina to the brain during development of visual system.…”
Section: Physiological Roles Of Insulin Receptor and Igf-i Receptor Isupporting
confidence: 48%
“…A simple interpretation of these results is that carvedilol may stimulate the translational or posttranslational step(s) of Na ϩ channel synthesis or may inhibit the internalization/degradation of Na ϩ channels. Yamamoto et al (1996) also observed that treatment of cultured adrenal medullary cells with insulin up-regulates the functional Na ϩ channels without causing any change in the level of mRNA encoding the Na ϩ channel ␣-subunit. In the present study, brefeldin A, an inhibitor of vesicle-mediated externalization of newly synthesized proteins from the trans-Golgi network, abolished the up-regulation of Na ϩ channels by carvedilol (Fig.…”
Section: Suppression Of Namentioning
confidence: 86%
“…22 Na ϩ influx was measured by incubating the cells with 2 Ci 22 NaCl at 37°C for 5 min in 1 ml of KRP buffer in the absence or presence of veratridine, ouabain, PbTx-3, and nicotine. The cells were washed with ice-cold KRP buffer, solubilized in 10% Triton X-100, and counted for radioactivity (Wada et al, 1986(Wada et al, , 1992Yamamoto et al, 1996Yamamoto et al, , 1997Yanagita et al, 1996;Yuhi et al, 1996;Shiraishi et al, 2001a,b).…”
Section: Methodsmentioning
confidence: 99%